Criminal Law Accountability in the Application of Artificial Intelligence in the Digital Era - Agus Sugiarto (Jurnal Multidisiplin Sahombu, 2024)
The development of technology and artificial intelligence (AI) has changed the social, economic and legal landscape significantly, especially in the context of the digital era. Artificial intelligence is now an integral part of various aspects of life, including the legal system. However, along with this progress, serious questions also arise regarding criminal law liability in the application of artificial intelligence. This research aims to analyze the dynamics of criminal legal liability that arise in the context of the application of artificial intelligence in the digital era. The research method used is normative legal analysis and literature study. The research results show that in the context of criminal liability related to the use of AI, there are complexities that must be considered carefully. Although AI may be able to carry out unlawful actions or decisions, it does not have the same consciousness or intent as humans. Therefore, in determining the criminal liability of AI, it is necessary to carefully consider how AI can be regulated and held responsible in a legal context. The importance of involving various stakeholders from various fields in discussing and forming regulations related to the use of AI is also a crucial point found in the results of this research.